PARENTAL COMMERCIAL MAIZE SELECTION FOR SILAGE PRODUCTION - CHAVES, LUCIANA GONÇALVES; MIRANDA, GLAUCO VIEIRA; SOUZA, LEANDRO VAGNO DE; GOMES, ODILON PEREIRA; OLIVEIRA, JACKSON SILVA E (International Journal of Maize & Sorghum, 2010)
The objectives of this study were to select maize genitors and determine the selection strategy for obtaining high quality silage maize hybrids. An experiment was conducted involving 45 hybrids obtained using a diallel scheme among commercial hybrids and four controls, in a triple lattice 7 x 7 design. The general combining ability (GCA) and specific combining ability (SCA) were significant for dry matter yield (DMY) and crude protein (CP), indicating additive and non-additive gene effects in genetic control. Only GCA was significant for plant height (PH), green matter yield (GMY) and hemicelluloses (HEM), which indicates a greater importance of additive than non-additive genetic effects in genetic control. The GCA and SCA of neutral detergent fiber (NDF) and acid detergent fiber (ADF) did not differ significantly between the hybrids, but there was a variance of 33% to 49% for NDF and 15 to 24% for ADF. The cultivars P30F90 and SHS4070 were the most recommended for increasing PH, GMY and DMY, while 2B619 and DKB466 were recommended to increase CP, and BRS3003 and AG1051 to reduce HEM. The hybrid combinations XB8028 x DKB 466, Valent x CD307, Valent x DKB466, SHS4070 x AG1051, BRS3003 x 2B619 and 2B619 x AG1051 are promising for maize silage production, because of their associated productive and qualitative traits.